Industrial robotics - Cook, Jerome T.; Stauffer, Robert; Society of Manufacturing Engineers ([Michigan] : Society of Manufacturing Engineers, 2004)
This program covers the array of robot configurations and features segments on key manufacturing applications using robots, end effector hand/gripping devices, end effector tools, online and offline robot programming and advantages and disadvantages of industrial robots
Title from title screen
Executive producer, Steven R. Bollinger
Keywords: Robots, Industrial; Robotics; Manufacturing processes